GENDER HUMOR DISCOURSE IN ‘FRIENDS’ COMEDY SERIES - Lailan Syafrina Dewi; Anni Holila Pulungan; Widya . Andayani (LINGUISTIK TERAPAN, 2022)
ABSTRACT This study deals with Gender Humor Discourse in ‘Friends’ Comedy Series. The aims of the study are 1) to categorize the types of gender humors used in ‘Friends’ comedy series, 2) to describe how gender humors realized in ‘Friends’ comedy series, and 3) to explain the reason of realizing gender humors in  ‘Friends’ comedy series in the ways they are. The study used a qualitative descriptive method and a critical discourse analysis approach. The data of the study is drawn from scripts consisted clauses of gender humor discourse in ‘Friends’ comedy series. The techniques for collecting data were observing the plot of the comedy series and selecting episodes which the one that contained the most humor in friendship then download the episodes selected to be observed, after that make documentations by trimming the scenes for making the transcript of dialogues from cut scenes and finding expressions appeared of all players in the comedy series to be observe. The results of study found that there were twenty-six clauses consisted humor types found in this study namely: Self-defeating types were eight (31%). Aggressive types were seven (27%), Affiliative types were six (23%) and elf-enhancing types were five (19%), It can be concluded that Self-defeating types became had high frequency in ‘Friends’ comedy series. From  forty-three clauses in ‘Friends’ comedy series, there were nine form of ten humor form realized in ‘Friends’ comedy series, they are Pun form, Riddle form, Joke form, Satire form, Anecdote form, Farce form, Irony form, Sarcasm form, and Wit form. From nine forms of verbal humor, Farce form became had high frequency in the kind of verbal humor of ’Friends’ comedy series. Finally the last study results, there were three reason of realizing humors discourse namely: Universal joke, Cultural Joke, and Linguistic joke.